Environmental Graphic Design and the Travelers Perception on the Exit Patterns of Subway Stations in Bangkok - Pakachart Puttipakorn; Prapatpong Upala (My University, 2017)
The purpose of this study was to investigate the design of the exit of MRT Subway, Chalerm Ratchamongkol route. The physical analysis indicated that the station could be grouped the physical design into four categories of total 18 stations. Which have evidence many differences in physical characteristics and may cause problem and confusion in gestalt theory routing for passengers. These finding showed that the graphic design and elements which will lead to the displaying of directional information to guide the path for travelers to decide to the exit of each side.Keywords: Environmental Graphic Design; Signage; Way-finding; Mass transit station.ISSN: 2398-4287© 2017. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.
Keywords: Signage; Association (psychology); Spatial Cognition and Navigation